Unintended hedging in ambiguity experiments - Oechssler, Joerg; Roomets, Alex (Economics letters, 2014)
We describe an ambiguity hedging problem in Ellsberg experiments, where combinations of individually ambiguous bets eliminate aggregate ambiguity, and which may yield incorrect classifications of ambiguity averse subjects. We propose a new classification consistent with this hedging possibility.
Available online 4 December 2013
Gesehen am 08.10.2020
We thank Peter Duersch, Adam Dominiak, Jürgen Eichberger, Yoram Halevy, PJ Healy, Jean-Philippe Lefort, Christoph Kuzmics, Stefan Trautmann, and ananonymous referee, as well as seminar audiences in Heidelberg, Copenhagen, Bielefeld, and at the ESA meeting Santa Cruz, 2013 for very helpful comments